Studi Aspirasi Warga Komunitas Miskin Penambang Batu dan Pemecah Batu Suplit di Kecamatan Moramo Utara Kabupaten Konawe Selatan - Darmin Tuwu (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2015)
Poverty is a complex social problem because it involves various aspects of life such as the right to the fulfillment of the needs of food, clothing, health, education, employment, and others. To overcome the problems of poverty, it cannot be relied on temporary charitable support, but need to be accompanied by programs to empower the poor, where the results can be enjoyed in the long term. This paper aims to identify and to explain aspirations, needs, and problems experienced by citizens of migrants from Central Java and West Java. The migrants are categorized as poor communities who work in mining as stone crusher suplit in District Moramo, South Konawe. The results showed that the high work ethic of miners’ workers and suplit stone crusher, however their socio-economic conditions are very poor rather than groups of farmers and fishermen. There are particular backgrounds that cause it to happen. First, the low wage which is not equal with the long working hours and job risks. Second, compared to groups of farmers and fishermen, rock crushers suplit citizens rarely gets help from the government, either in the form of capital assistance, as well as skill training program. Third, there is no empowerment program introduced to them, so that they are empowered or able to switch professions with better income. These conditions make the workers of stone crushers suplit difficulty to lift the dignity and status, and to improve their quality of life, so that they will continuously be in a